Convention on Biological Diversity and Nagoya Protocol: historical development and public health implications - Wei-yu ZHOU; Bai-chu GUAN; Yi-han LU (Editorial Office of Chinese Journal of Public Health, 2023)
Convention on Biological Diversity of the United Nations came into force in 1993. In order to further achieve the goal of access and benefit-sharing (ABS) in the area of microbial resources, Conference of the Parties to the Convention on Biological Diversity in 2014 adopted the Nagoya Protocol. We attempt to sort out historical process of the Convention and the Protocol and to analyze ABS issue of pathogen in infectious disease prevention and control in detail for conducting public global health cooperation based on biodiversity and improving domestic laws and regulations on the sharing of microbial resources.